The Pathogenic Role of Expanded CD8⁺CD28null Angiogenic T Cells in ANCA-Associated Vasculitis - Haomiao Shen; Jinlin Miao; Haoyang Sun; Kui Zhang; Renli Liu; Zichao Li; Leyang Zhang; Peiyan Zhang; Jiawei Wang; Bei Zhang; Longyu Chen; Zhaohui Zheng; et al. (Biomedicines)
Objectives: Angiogenic T cells (Tang) are crucial in promoting angiogenesis, with the loss of CD28 serving as a marker for highly differentiated and senescent T cells. This study aims to investigate the characteristics and potential roles of CD8+CD28null Tang in patients with ANCA-associated vasculitis (AAV). Methods: A cohort of AAV patients and matched healthy controls (HCs) were analyzed. Flow cytometry was used to assess the profiles of circulating CD8+CD28null Tang. In vitro functional assays were performed to evaluate the pathogenic properties of CD8+CD28null Tang. Results: CD8+CD28null Tang levels were significantly higher in the peripheral blood of AAV patients compared to HCs, and their levels were further increased in AAV patients with MPO⁺, p-ANCA⁺, or interstitial lung disease compared to their respective control groups. Additionally, there was a positive correlation between both the percentage and absolute count of CD8+CD28null Tang and the Birmingham Vasculitis Activity Score (BVAS). In patients with a good treatment response, both the percentage and absolute count of CD8+CD28null Tang were significantly reduced, and this reduction was positively correlated with the decrease in BVAS scores. In vitro studies revealed that CD8+CD28null Tang displayed enhanced chemotactic properties, induced apoptosis in human umbilical vein endothelial cells (HUVECs), and inhibited their proliferation, migration, and tube formation. Conclusions: AAV patients exhibit increased levels of circulating CD8+CD28null Tang, which can be reduced following effective treatment. Furthermore, CD8+CD28null Tang may contribute to the pathogenesis of AAV by promoting apoptosis and inhibiting the proliferation, migration, and tube formation of HUVECs.